Theoretical Study: Quality of Profit - Rusmianto Rusmianto (Politeknik Negeri Lampung, 2014)
Quality of profit refers to how far the value of profit of a company can communicate its performance during a period of measurement representatively and reliably (Sivaramakrishnan, 2008). Quality of profit can also be understood as the ability of the profit reported to predict future performance (Yaghoobnezhad, 2012). Some approaches can be used to measure the quality of a profit, such as : discretionary accruals, accrual quality, absolute residual accrual quality, and Value relevance. In addition, there are some factors influencing profit quality namely: state ownership, gender, dividend, corporate characteristics, and corporate governance mechanism.Keywords: profit quality, discretionary accruals, accrual quality